Pelatihan Keterampilan Menulis dalam Korespondensi Berbahasa Inggris, Menerjemahkan serta Keterampilan Menggunakan Grammarly, Google Translate, dan Google Drive di Sekolah Menengah Kejuruan KSATRYA, Rawasari, Jakarta Pusat - Elfa Setiawan; Dinda A Rahman; Rudi Kristanto (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
The development of the world of education in the 21st century is now entering an era marked by the onslaught of the information technology revolution and the formation of the economic order and global relations, thus demanding an output of educational outcomes and outcomes that are in line with the demands of the world of work. The ability to communicate both in Speaking and writing is one of the abilities that must be mastered by everyone.The purpose of this Community Service Activities is to provide understanding and skills to vocational students in improving English language skills, particularly written communication skills in the business world as well as practical skills in translating documents documents or articles in English. The achievements of this service are increasing knowledge, insight, and English correspondence skills among vocational high school students, optimizing the use of online-based English Learning Tools such as Google Translate, Grammarly and Google Drive. The training activity was held for 4 hours on October 30, 2019, in the form of lectures, question-answers, and hands-on practice using Translation Tools. There were 22 trainees, class XII students of SMK Ksatrya, Cempaka Putih Barat, Central Jakarta. Based on the feedback from the participants, the training activities are very good and beneficial for them.This activity is not only limited to the training but is expected to be the beginning of the collaboration between the STIAMI Institute and the Ksatrya Vocational School in the future, to conduct other English language training with different topics or themes.